(untitled) (Biological Sciences - PJSIR, 1995)
Seeds extract of Syzygium cumini or Eugeniajambolana, commonly known as Jaman was tested for its stress reducing properties. Aconsiderable positiveresponse ingeneral behaviourof testanimals wasobserved. Reduction in locomotion, decrease in aggressiveness of behaviour, dose dependent potentiation of phenobarbitone induced sleep- ing time, significant analgesic action against acetic acid induced writhing movement and reduction in body tempera- tures were noted. A significant reduction in the stress induced elevated corticosterone level was observed which is a reliable indicator of stress.